ISLAM (DI) NUSANTARA; ESENSI, GENEALOGI SERTA IDENTITASNYA ISLAM (IN) ARCHIPELAGO; ITS ESSENCE, GENEALOGY, AND IDENTITY - Syauqi, Muhammad Labib (Analisis: Jurnal Studi Keislaman, 2015)
This paper tries to explain about the details of Islam of Archipelago which  is now  getting   the  momentum  back,  even  though  the initial  idea about Islam of Archipelago  is not really new. Islam of  Archipelago   attempts   to make  a  dialogue  from  religious text  which  comes  from  the  revelation with  local  contents  on earth, to actualize  limited  text  of religion with unlimited  social phenomenon in society. Islam of Archipelago is on the effort to find the possible various interpretations without changing the law itself.  Because the existence  of text  is limited  whereas a social phenomenon is unlimited, even it is dynamically developing, the process of dynamic dialectic proves that  Islam is appropriate  in any place and everlasting any time.